12 Clinical and radiological features of COL4A1 disease. Issue 3 (15th February 2011) - Shah, S; McLean, B; Ellard, S; Churchill, A; Kneen, R; Lim, M; Rankin, J; Stoodley, N; van der Knaap, M S; Whitney, A; Jardine, P
Abstract : Background: Mutation in the collagen gene COL4A1 is a newly recognised cause of cerebral small vessel disease leading to porencephaly and/or stroke. It is inherited as an autosomal dominant trait and has a wide inter and intrafamilial variation in presentation. We present the details of 5 UK families with a COL4A1 mutation. Results: Presentation of index case was recurrent stroke in 2/5 at age 14 years and 4 years, infantile hemiplegia in 2/5 and infantile spasms in 1/5. Stroke occurred following a surgical procedure under general anaesthesia in 2 families. A history of migraine was present in family members in 3/5 families. Congenital cataracts with/without anterior segment dysgenesis was present in 4/5 cases and nystagmus was present in the 1 case without cataracts. MRI showed leukoencephalopathy involving deep white matter in 5/5 cases and porencephaly in cases with infantile hemiplegia. Gradient echo detected microhaemorrhages. A COL4A1 mutation was confirmed in all index cases. The same mutation in exon 30 leading to the same phenotype was found in 2 cases. Conclusion: We suggest that COL4A1 mutation should be considered in individuals with 2 or more features of leukoencephalopathy, porencephaly, micro or macrohaemorrhages or cataracts/anterior segment dysgenesis especially if a family history is present. We propose an investigation protocol to look for the various features of the disease. General anaesthesia might be a risk factor for strokes.